Technical teams as commoning gatekeepers: The case of IATS in Mutual Aid Housing Cooperatives in Uruguay - Irene Valitutto; Ignacio De Souza Lopez (International Journal of the Commons)
This paper tries to assess the relevance of intermediary technical stakeholders drawing from the experience of Uruguayan mutual aid housing cooperatives (Cooperativas de Viviendas por Ayuda Mutua – MAHCs). Their Institutes for Technical Assistance (Institutos de Asistencia Técnica – IATs), which promoted and fostered this housing model, continue, to this day to support the endurance of MAHCs’s experiences and communal principles. The study focuses on IATs’ working practices, which foster participatory processes through knowledge transfer and co-creation with cooperative members. It explores the intermediary role of IATs between the cooperative community and policymakers, positioning them as gatekeepers of the commoning process. Central to this analysis is the concept of “participatory accompaniment,” which serves as the key instrument in the IATs’ intermediary function.